Hydrogeochemical analysis and evaluation of groundwater quality in the Gadilam river basin, Tamil Nadu, India - Prasanna, Mohan Viswanathan; Chidambaram, S.; Hameed, A.; Srinivasamoorthy, K. (INDIAN ACAD SCIENCES, C V RAMAN AVENUE, SADASHIVANAGAR, P B #8005, BANGALORE 560 080, INDIA, 2011)
Water samples were collected from different formations of Gadilam river basin and analyzed to assess the major ion chemistry and suitability of water for domestic and drinking purposes. Chemical parameters of groundwater such as pH, electrical conductivity (EC), total dissolved solids(TDS), Sodium (Na+), Potassium (K+), Calcium (Ca+), Magnesium (Mg+), Bicarbonate (HCO -3 ), Sulphate (SO -4 ), Phosphate (PO -4 ) and Silica (H4SiO4) were determined. The geochemical study of the aquatic systems of the Gadilam river basin show that the groundwater is near-acidic to alkaline and mostly oxidizing in nature. Higher concentration of Sodium and Chloride indicates leaching of secondary salts and anthropogenic impact by industry and salt water intrusion. Spatial distribution of EC indicates anthropogenic impact in the downstream side of the basin. The concentration levels of trace metals such as Iron (Fe), Lead (Pb), Nickel (Ni), Bromide (Br), Iodide (I) and Aluminium (Al) have been compared with the world standard. Interpretation of data shows that some trace metals such as Al, Ni and Pb exceed the acceptable limit of world standard. Geophysical study was carried out to identify the weathered zone in the hard rock and contaminated zone by anthropogenic impact in the downstream of river Gadilam. A few of the groundwater samples in the study area were found to be unsuitable for domestic and drinking purposes.